Exposure to War and Its Labor Market Consequences over the Life Cycle - Sebastian Till Braun; Jan Stuhler (Institute of Labor Economics (IZA), 2023)
With 70 million dead, World War II remains the most devastating conflict in history. Of the survivors, millions were displaced, returned maimed from the battlefield, or spent years in captivity. We examine the impact of such wartime experiences on labor market careers and show that they often become apparent only at certain life stages. While war injuries reduced employment in old age, former prisoners of war postponed their retirement. Many displaced workers, particularly women, never returned to employment. These responses are in line with standard life-cycle theory and thus likely extend to other conflicts.
Keywords: J24; J26; N34; 330; World War II; labor market careers; war injuries; prisoners of war; displacement; life-cycle models